2013
DOI: 10.1038/cddis.2013.351
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of polyglutamine protein toxicity by co-expression of a heat-shock protein 40 and a heat-shock protein 110

Abstract: A network of heat-shock proteins mediates cellular protein homeostasis, and has a fundamental role in preventing aggregation-associated neurodegenerative diseases. In a Drosophila model of polyglutamine (polyQ) disease, the HSP40 family protein, DNAJ-1, is a superior suppressor of toxicity caused by the aggregation of polyQ containing proteins. Here, we demonstrate that one specific HSP110 protein, 70 kDa heat-shock cognate protein cb (HSC70cb), interacts physically and genetically with DNAJ-1 in vivo, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 57 publications
(84 reference statements)
0
65
1
Order By: Relevance
“…Addition of G85R SOD1YFP to squid axoplasm inhibits anterograde axonal vesicle transport, but purified human Hsp110 (HspA4L) prevents this effect even when added at substoichiometric amounts relative to the misfolded protein, suggesting that it cooperates with endogenous Hsc70 and DnaJ homologs to dissociate toxic oligomeric forms (21). In studies in Drosophila eye, transgenic expression of either Drosophila Hsp110 or human Hsp110 (HspA4L; APG1) was able to rescue toxicity from coexpressed polyQ-expanded proteins (22,23). As mentioned, in motor neurons of the G85R SOD1YFP line, one of three endogenous mouse Hsp110 RNAs, HspH1, is induced approximately twofold compared with wtSOD1YFP motor neurons, one of the few RNAs observed to be altered (3).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of G85R SOD1YFP to squid axoplasm inhibits anterograde axonal vesicle transport, but purified human Hsp110 (HspA4L) prevents this effect even when added at substoichiometric amounts relative to the misfolded protein, suggesting that it cooperates with endogenous Hsc70 and DnaJ homologs to dissociate toxic oligomeric forms (21). In studies in Drosophila eye, transgenic expression of either Drosophila Hsp110 or human Hsp110 (HspA4L; APG1) was able to rescue toxicity from coexpressed polyQ-expanded proteins (22,23). As mentioned, in motor neurons of the G85R SOD1YFP line, one of three endogenous mouse Hsp110 RNAs, HspH1, is induced approximately twofold compared with wtSOD1YFP motor neurons, one of the few RNAs observed to be altered (3).…”
Section: Discussionmentioning
confidence: 99%
“…29 We recently expressed Hsp70 or Hsp104 in a Drosophila model of spinocerebellar ataxia. 14 Here, Hsp104 suppressed toxicity after the onset of polyglutamine-induced degeneration.…”
Section: Applying Chaperones To Restore Proteostasismentioning
confidence: 99%
“…They illustrate how molecular genetic approaches can assess whether up-and downregulation of target genes of special interest can modulate the toxicity of a disease protein and thereby contribute to disease progression. These and other studies have revealed a number of effects of various molecular chaperone proteins, chaperone helper proteins, and protein quality control pathways on disease pathogeneisis in fly models (Warrick et al 1999;Chan et al 2000;KazemiEsfarjani and Benzer 2000;Vos et al 2010;Kuo et al 2013). These studies have also revealed links between the ubiquitin-proteasome pathway and autophagy pathways, as these processes dynamically interact in vivo to affect protein degradation, normally and in disease (Pandey et al 2007).…”
Section: Establishing a Modelmentioning
confidence: 92%